4-TH International conference on "environmental protection in Mechanical Engineering" - KACPROWSKI, Janusz (Archives of Acoustics, 1978)
The 4-th Conference, held April 11-13, 1978, at Gyor (HPR), was dedicated to the problems connected with a broadly conceived environmental protection against harmful effects and consequences of production processes and technical, technological and communication equipment encountered chiefly in the mechanical engineering. The Conference was sponsored by the local section in Gyor of the Hungarian Scientific Society of Mechanical Engineers in cooperation with the local section of the Hungarian Optical, Acoustical and Film Technical Society (OPAKFI), as also with the Board for the Matters of Natural Environment at Gyor. Chairman of the Organizational Committee was Mr. J. Jambor, Secre-tary General Mr. E. Varga. The deliberations took place in the Cultural Centre Raba at Gyor, Szecheny Square 7.